Symmetric differentiation on time scales - Brito da Cruz, A. M. C.
We define a symmetric derivative on an arbitrary nonempty closed subset of the real numbers and derive some of its properties. It is shown that real-valued functions defined on time scales that are neither delta nor nabla differentiable can be symmetric differentiable. © 2012 Elsevier Ltd. All rights reserved.